Education, leadership and partnerships: nursing potential for Universal Health Coverage - Isabel Amélia Costa Mendes; Carla Aparecida Arena Ventura; Maria Auxiliadora Trevizan; Leila Maria Marchi-Alves; Valtuir Duarte de Souza-Junior (Universidade de São Paulo, 2016)
Objective: to discuss possibilities of nursing contribution for universal health coverage. Method: a qualitative study, performed by means of document analysis of the World Health Organization publications highlighting Nursing and Midwifery within universal health coverage. Results: documents published by nursing and midwifery leaders point to the need for coordinated and integrated actions in education, leadership and partnership development. Final Considerations: this article represents a call for nurses, in order to foster reflection and understanding of the relevance of their work on the consolidation of the principles of universal health coverage.